2009
DOI: 10.1088/0022-3727/42/11/115002
|View full text |Cite
|
Sign up to set email alerts
|

Large perpendicular exchange bias in IrMn/CoFe/[Pt/Co] multilayers grown on a Ta/Pt buffer layer

Abstract: Bottom pinned IrMn/[Co/Pt] multilayer films with relatively thin Pt layers (∼10 Å) grown on a Ta/Pt buffer have been found to exhibit favourable perpendicular exchange bias (PEB) and well-defined perpendicular anisotropy at room temperature. However, even the optimum film suffers from the same problem as those reported previously, i.e. the exchange bias field is just slightly larger than the coercivity. By replacing the Co layer in contact with IrMn by a 6–8 Å Co60Fe40 layer, the exchange bias is drastically e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 22 publications
3
21
0
Order By: Relevance
“…The exchange anisotropy energy J K , de ned as J K = M S ·t FM ·H EX (where M S is the saturation magnetization, t FM is the FM layer thickness, and H EX is the exchange bias eld), can exceed 0.4 mJ/m 2 15) . Perpendicular exchange bias has been reported in several systems using other AFM layers such as CoO 21) , NiO 22) , FeF 2 23) , MnPd 24) , Fe-Mn [25][26][27] , and Ir-Mn 26,[28][29][30][31] . 25,26) and Fe-Co 30,31) between their Pt/Co multilayers and Ir-Mn layers.…”
Section: Perpendicular Exchange Bias Induced By Cr 2 O 3 (0001)mentioning
confidence: 90%
“…The exchange anisotropy energy J K , de ned as J K = M S ·t FM ·H EX (where M S is the saturation magnetization, t FM is the FM layer thickness, and H EX is the exchange bias eld), can exceed 0.4 mJ/m 2 15) . Perpendicular exchange bias has been reported in several systems using other AFM layers such as CoO 21) , NiO 22) , FeF 2 23) , MnPd 24) , Fe-Mn [25][26][27] , and Ir-Mn 26,[28][29][30][31] . 25,26) and Fe-Co 30,31) between their Pt/Co multilayers and Ir-Mn layers.…”
Section: Perpendicular Exchange Bias Induced By Cr 2 O 3 (0001)mentioning
confidence: 90%
“…Many researchers have tried to improve the PEB using different methods. For example, Liu et al 15 obtained a high PEB field of about 95 mT by inserting a CoFe layer between IrMn and Co/Pt multilayers at room temperature. Wang et al 16 reported a large PEB effect in CoPt/CoO multilayers at low temperature.…”
mentioning
confidence: 99%
“…This result is not in agreement with the results obtained for small cooling fields and with results obtained on other systems. [22,[26][27][28] However, positive EB associated with a weak interface coupling has as well been observed before in FeF 2 /Fe system for the cooling field of about 0.2 T. [29] A study of the effect of the cooling field on the EB field was conducted on FeF 2 /Fe system by Nogues et al [30] It has been shown that the EB field becomes positive for very strong cooling field values while it is negative for weak cooling fields. The magnitude of the cooling field needed to obtain a positive shift depends strongly on the interface coupling at the FM/AFM interface.…”
Section: Heat-treated Samplesmentioning
confidence: 60%